PENGARUH DISCOVERY LEARNING BERBASIS MEDIA SCRAPBOOK 3D TERHADAP MOTIVASI DAN HASIL BELAJAR - Sari, Dian Ratna; Kamidjan, Kamidjan; Raharja, Hawwin Fitra (Prodi PGSD Fakultas Ilmu Pendidikan (FIP) Universitas Hasyim Asy'ari (Unhasy) Tebuireng Jombang, 2020)
Discovery learning learning model is an effective model for advancing student motivation and learning outcomes. The aim of this research is to understand the effect of discovery learning model based on 3D scrapbook media on building material on student motivation and learning outcomes of fifth grade students at SDN Munungkerep II Kabuh. This type of research uses a quantitative approach, the research design that is used is the post-test only control design. The population in this study was fifth grade students of SDN Munungkerep Kabuh Jombang with saturated sampling techniques. The data analysis techniques that are used are validity test, normality test, and multivariate variant test (MANOVA). The results showed that (1) The application of discovery learning model based on 3D scrapbook media on space building material influenced the motivation of class students based on a significant value of 0.193 ≥ 0.05, (2) The application of discovery learning model based on 3D scrapbook media on space building material affect the learning outcomes of class students based on a significant value of 0.246 ≥ 0.05, and (3) The application of discovery learning models using 3D scrapbook media on building materials has an effect on motivation and student learning outcomes based on a significant value of 0.433 ≥ 0.05.